An enhanced dynamic model of battery using genetic algorithm suitable for photovoltaic applications. (1st May 2016) - Blaifi, S.; Moulahoum, S.; Colak, I.; Merrouche, W.
Highlights: We proposed a developed dynamic battery model suitable for photovoltaic systems. We used genetic algorithm optimization method to find parameters that gives minimized error. The validation was carried out with real measurements from stand-alone photovoltaic string. Abstract: Modeling of batteries in photovoltaic systems has been a major issue related to the random dynamic regime imposed by the changes of solar irradiation and ambient temperature added to the complexity of battery electrochemical and electrical behaviors. However, various approaches have been proposed to model the battery behavior by predicting from detailed electrochemical, electrical or analytical models to high-level stochastic models. In this paper, an improvement of dynamic electrical battery model is proposed by automatic parameter extraction using genetic algorithm in order to give usefulness and future implementation for practical application. It is highlighted that the enhancement of 21 values of the parameters of CEIMAT model presents a good agreement with real measurements for different modes like charge or discharge and various conditions.